Analysis of the Effectiveness of Condenser Heat Transfer in the Distillation Process of Serai Wangi Leaves - Karo Karo, Septa Fernando; Weriono; Din Aswan Ritonga; Darianto, Darianto; Muhammad Idris; Indra Hermawan (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2024)
The condenser is a critical component in systems designed to condense steam into liquid. The performance of a condenser can be influenced by the rate of heat transfer, vacuum pressure, and effectiveness. The aim of this research is to ascertain the effectiveness value and the variables affecting the performance of the condenser in the distillation process of citronella leaves, as well as to understand the impact of the heat transfer rate on film condensation (condensate steam mass). The methodology for assessing effectiveness values utilized the Log Mean Temperature Difference (LMTD) and Effectiveness – Number of Transfer Unit (NTU) approaches, alongside comparing the condensate steam mass with the steam mass flow rate to achieve film condensation. The research findings revealed an effectiveness value of 89% for the condenser, with 36% of the condensate steam mass converting into bio-oil. Influential variables include a capacity ratio of 0.0182840 and a heat transfer rate of 186,544.68 W. The LMTD was calculated to be 29.74°C. Thus, it can be concluded that the condenser used in the distillation process of citronella leaves still maintains good performance.